Sustainability Reporting and Investors' Perception: Evidence from Selected Sectors in Nigeria - Ajasa-Adeoye, Fadekemi; Osamor, Ifeoma Patricia; Godwin, Omoregbee; Oyetunji, Honour Oyedoyin; Adeoye, Samuel; Mhlongo, Vutomi Maureen (PT Global Digital Sains Tekno, 2026)
Purpose: The study aimed to investigate the effect of sustainability reporting on investors’ perceptions in Nigeria, specifically examining how environmental, social, and governance (ESG) disclosures influence the Price Earnings (P/E) ratio of listed firms. Method: An ex-post facto research design was employed using panel data from ten listed firms in the oil and gas and industrial goods sectors between 2015 and 2024. Data were collected from annual reports, sustainability reports, and NGX sources. ESG disclosure indices were constructed and normalized. Panel regression techniques were applied, with the Hausman test supporting the use of fixed effects. Findings: The results revealed that environmental, social, and governance disclosures had a positive and significant effect on the P/E ratio. The combined ESG model explained 34.56% of the variation in P/E ratios, indicating that sustainability reporting is value-relevant for investors. Implication: The study recommends that firms enhance the quality of ESG disclosures and that regulators promote standardized reporting practices. Such measures would improve market transparency and strengthen investor confidence in Nigeria’s capital market. Originality: This research provides empirical evidence from Nigeria, highlighting the direct link between sustainability reporting and investor valuation metrics. It contributes to the literature by demonstrating the relevance of ESG disclosures in shaping investor perceptions in emerging markets.